2021
DOI: 10.3390/app112210844
|View full text |Cite
|
Sign up to set email alerts
|

Local Failure Modes and Critical Buckling Loads of a Meta-Functional Auxetic Sandwich Core for Composite Bridge Bearing Applications

Abstract: This paper presents a novel meta-functional auxetic unit (MFAU) cell designed to improve performance and weight ratio for structural bridge bearing applications. Numerical investigations were conducted using three-dimensional finite element models validated by experimental results. The validated models were exposed to compression and buckling actions to identify structural failure modes, with special attention placed on the global behaviours of the meta-functional auxetic (MFA) composite bridge bearing. This b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Another benefit of using TPMS structures is that these structures exhibit a uniform stress distribution, whilst struct-based structures can undergo stress concentrations close to the joints of the structs [24][25][26][27]. In the same way, from our previous work [6,15], local failures of struct-based structures are likely to occur before yielding under compression. Lei Zhang et al [27] found that TPMS structures exhibited a better stiffness, plateau stress, and energy-absorption ability to struct-based body-centred cubic (BCC) lattices.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Another benefit of using TPMS structures is that these structures exhibit a uniform stress distribution, whilst struct-based structures can undergo stress concentrations close to the joints of the structs [24][25][26][27]. In the same way, from our previous work [6,15], local failures of struct-based structures are likely to occur before yielding under compression. Lei Zhang et al [27] found that TPMS structures exhibited a better stiffness, plateau stress, and energy-absorption ability to struct-based body-centred cubic (BCC) lattices.…”
Section: Introductionmentioning
confidence: 73%
“…Furthermore, in order to afford to eliminate the failure patterns of both SLEBBs and UFLEBBs as previously mentioned, the development of a proposed novel bridge bearing model has been considered in this paper. Nowadays, the use of 3D-printed complex structural components using lattice structures applied in civil engineering is rapidly becoming attractive [15]. Among the various lattice structures presented in Figure 2, the triply periodical minimal surface (TPMS) structures which are among those lattice structures have received considerable attention with potential advantages throughout struct-based lattices (also known as TPMS lattices such as schwarz primitive (SP), gyroid, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Sengsri and Kaewunruen [7] highlighted a novel meta-functional auxetic unit (MFAU) cell designed to improve performance and weight ratio for structural bridge bearing applications. Robust numerical simulations were conducted using three-dimensional finite element models validated by full-scale experimental results.…”
Section: Insights Into Materials Behavioursmentioning
confidence: 99%
“…At this point, in terms of better designs for bridge bearing applications, the development of 3D-printed TPMS bridge bearings under any static and dynamic loading has been inspired by eliminating the aforementioned problems. Based on our previous works [1,[14][15][16][17][18], the use of 3D-printed TPMS structures, which have a relatively higher performance-to-weight ratio, has been considered for bridge bearing applications, resulting in improving their behaviours under any anticipated loading, compared to traditional bearings.…”
Section: Introductionmentioning
confidence: 99%